2019
DOI: 10.5897/ijmms2018.1392
|View full text |Cite
|
Sign up to set email alerts
|

Arousal perception/misperception and total sleep time misperception in subjects with sleep disorders

Abstract: Limited studies have examined arousal perception in obstructive sleep apnea (OSA) or other sleep disorders. The aim of this study is to evaluate the factors that affect patients' arousal and total sleep time perception. This is a retrospective study of 210 subjects divided into 5 groups: Primary insomnia; upper airway resistance syndrome (UARS)/primary snoring; mild, moderate and severe OSA. Perceived arousals were compared to objectively defined arousals. The subjects' age, body mass index (BMI), total sleep … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, another study reported contradictory results wherein no difference was found with regard to the microarchitecture of sleep between subjects with OSA and insomnia. 8 Khan et al 9 extended the scope by comparing sleep architecture between subjects with varying severity of insomnia and reported that sleep architecture was comparable among groups.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, another study reported contradictory results wherein no difference was found with regard to the microarchitecture of sleep between subjects with OSA and insomnia. 8 Khan et al 9 extended the scope by comparing sleep architecture between subjects with varying severity of insomnia and reported that sleep architecture was comparable among groups.…”
mentioning
confidence: 99%
“…However, literature addressing this issue is scanty, and after a careful search, we could find only three studies that compared sleep architecture between subjects with insomnia and OSA. 6 , 8 , 9 A recent systematic review and meta-analysis suggested that though a decent amount of literature is available from other regions regarding COMISA, literature from the South-East Asia region is scarce. 5 There is a need for filling this void considering the difference in body-mass index, craniofacial architecture, and sleep patterns of the Asian population vs. Caucasian population.…”
mentioning
confidence: 99%